Fully passivated radial junction nanowire silicon solar cells with submerged nickel‐silicide contact for efficiency enhancement. Issue 12 (1st June 2013) - Ren, R.; Guo, Y.X.; Wang, J.; Zhu, R.H.
Abstract : Presented is a silicon solar cell model with fully passivated radial junction nanowire surface decoration and submerged nickel‐silicide contact. Numerical simulations using a finite‐difference time‐domain method have been done to investigate the spectral responses of the solar cell model. The experimental results indicate that, with proper nickel‐silicide thickness, the fill factor of the cell can be improved considerably without much degradation on short circuit current density. Under AM 1.5G illumination, the silicon nanowire solar cell device with 50 Å nickel‐silicide contact has short circuit current density of 26.3 mA/cm 2, open circuit voltage of 586 mV and fill factor of 70.0%, contributing to power conversion efficiency of 10.8%, which is 19% higher than the control device without the nickel‐silicide contact.